PERATURAN DAERAH NO 7 TAHUN 2018 TENTANG NAGARI PERIHAL KERAPATAN ADAT NAGARI PRESPEKTIF SIYASAH DUSTURIYAH - Jefry Jefry; Emrizal Emrizal; Siska Elasta Putri (Institut Agama Islam Negeri Batusangkar, 2022)
This article discusses the background of the birth of Regional Regulation Number 7 of 2018 concerning Nagari regarding Kerapatan Adat Nagari (KAN), duties and functions of Kerapatan Adat Nagari (KAN), and Fiqh Review of Siyasah Duturiyah on Regional Regulation No 7 of 2018 concerning Nagari regarding KAN. This research is a library research method. This study uses a normative legal research typology, namely examining legislation/theories and literature review of secondary data relating to the background of the birth of Regional Regulation No. 7 of 2018 concerning Nagari regarding KAN and a review of Fiqh Siyasah Duturiyah on Regional Regulation No. 7 the Year 2018. The results of this study conclude that the birth of the Regional Regulation has been initiated in Regional Regulation No. 2 of 2007 but has not covered all those related to the parts of the KAN. The issuance of Regional Regulation No. 7 of 2018 reaffirms the parts of the KAN which include Niniak Mamak, Alim Ulama, Cadiak pandai, Bundo kanduang, and Parik paga Nagari. Thus, Regional Regulation No. 7 of 2018 concerning Nagari provides an opportunity for regions to form villages (government) based on customs according to the rights of origin of the local customary law community unit. The view of Siyasah Duturiyah fiqh where the duties and functions of the KAN do not deviate from the Fiqh rules that have been set by Regional Regulations.